HCV seroconversion in a cohort of people who use drugs followed in a mobile harm reduction unit in Madrid: Breaking barriers for HCV elimination - Valencia La Rosa, Jorge; Ryan, Pablo; Alvaro-Meca, Alejandro; Troya, Jesús; Cuevas, Guillermo; Gutiérrez, Jorge; Moreno, Santiago (PloS one, 2018)
Harm reduction strategies have been shown to decrease the incidence of human immunodeficiency virus (HIV) infection in people who inject drugs (PWID), but the results have been inconsistent when it comes to prevention of hepatitis C virus (HCV) infection. We aimed to examine the rate of HCV seroconversion among people who use drugs (PWUD) followed at a mobile harm reduction unit (MHRU) to evaluate if a low-threshold methadone substitution program (LTMSP) is associated with a low HCV seroconversion rate and subsequently identify barriers for elimination. A cohort of PWUD have been followed at a MRHU in Madrid between 2013 and 2016. Individuals who were negative for HCV antibodies at baseline and who had at least one retest for HCV antibodies were eligible. Kaplan-Meier methods were employed to estimate the global incidence density. During the study period, 946 PWUD were screened for HCV at least once. At baseline 127 PWUD were negative for HCV antibodies and had at least one follow-up HCV antibodies test. The baseline HCV prevalence was 33%. After a median 0.89 (IQR 0.3-1.5) years of follow-up and 135 person-years of risk for HCV infection, 28 subjects seroconverted. The incidence density for HCV seroconversion for this sample was 20.7 cases (95% CI: 14.3-29.7) per 100 person-years. Injecting drugs in the last year was strongly associated to HCV seroconversion (AHR 15.5, 95%CI 4.3-55.8, p < 0.001). Methadone status was not associated to HCV seroconversion. A high incidence of HCV infection was found among PWUD at a MHRU in Madrid. In this setting opiate substitutive treatment (OST) as a LTMSP does not appear to protect against HCV seroconversion.